2000
DOI: 10.1038/sj.bjp.0703308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pulmonary eosinophilia and airway hyperresponsiveness in allergic mice by rolipram: involvement of endogenously released corticosterone and catecholamines

Abstract: 1 This study investigates the role of adrenal-derived catecholamines and corticosterone on the inhibition by rolipram, a phosphodiesterase (PDE)-4 inhibitor, of pulmonary eosinophilia and airway hyperresponsiveness (AHR) in allergic mice. 2 The following experimental groups were studied in mice sensitized and challenged with ovalbumin (OVA): normal, adrenalectomized, propranolol (b-adrenoceptor antagonist) and metyrapone (corticosterone synthesis inhibitor) treated. These interventions were studied both in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
(45 reference statements)
1
15
1
Order By: Relevance
“…These results were supported by findings from previous studies, in which inhibition of PDE-4 caused an increase in plasma corticosterone levels in rats (Kumari et al, 1997;Kung et al, 2000;Jabaris et al, 2015). Contrasting reports from previous studies demonstrated that exogenous administration of corticosterone and elevation of the hormone in circulation following stress exposure reduced hippocampal synaptic potentiation and hippocampus-specific learning and memory (Kim et al, 2001;Alfarez et al, 2002;Woodson et al, 2003).…”
Section: Discussioncontrasting
confidence: 77%
“…These results were supported by findings from previous studies, in which inhibition of PDE-4 caused an increase in plasma corticosterone levels in rats (Kumari et al, 1997;Kung et al, 2000;Jabaris et al, 2015). Contrasting reports from previous studies demonstrated that exogenous administration of corticosterone and elevation of the hormone in circulation following stress exposure reduced hippocampal synaptic potentiation and hippocampus-specific learning and memory (Kim et al, 2001;Alfarez et al, 2002;Woodson et al, 2003).…”
Section: Discussioncontrasting
confidence: 77%
“…In one study, the inhibitory effect of rolipram on TNF-␣ induction during streptococcal cell wall-induced arthritis was reversed by the GR antagonist, RU486 (Laemont et al 1999). In another study, the glucocorticoid synthesis inhibitor, metyrapone, was found to attenuate rolipram-induced inhibition of pulmonary eosinophilia in allergic mice (Kung et al 2000). Complementing these studies are a number of reports demonstrating comparable immunologic effects of glucocorticoids and rolipram on cytokine induction (decreased TNF-␣ and increased interleukin (IL)-10 and IL-4) as well as inflammation (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, rolipram does not appear to A number of studies have documented the wideranging effects of rolipram on cellular activity in both the immune system and the brain. Immunologic studies have shown that rolipram has potent antiinflammatory effects, exhibiting inhibition of the proinflammatory cytokine, TNF-␣, and providing protection from several autoimmune disorders (Ross et al 1997;Laemont et al 1999;Kung et al 2000;Knox 2000, 2001;Sekut et al 1995;Eigler et al 1998;Sommer et al 1997). Indeed, it has been suggested that rolipram may serve as an effective therapy for human autoimmune disorders, including multiple sclerosis (Sommer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were then tested for airway hyperresponsiveness to metacholine by the forced oscillation technique as previously described (21). A Student's t test was used to determine statistical significance between groups, with p Ͻ 0.5 being considered significant.…”
Section: Airway Hyperreactivitymentioning
confidence: 99%